2020
DOI: 10.1186/s12933-020-01015-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of small dense low-density lipoprotein with cardiovascular outcome in patients with coronary artery disease and diabetes: a prospective, observational cohort study

Abstract: Background: Elevation in small dense low-density lipoprotein (sdLDL) is common in patients with diabetes mellitus (DM), which has already been reported to be associated with incidence of coronary artery disease (CAD). The aim of the present study was to investigate the prognostic value of plasma sdLDL level in patients with stable CAD and DM. Methods: A total of 4148 consecutive patients with stable CAD were prospectively enrolled into the study and followed up for major cardiovascular events (MACEs) up to 8.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
(44 reference statements)
0
40
0
Order By: Relevance
“…Koba S et al recruited 482 stable CHD patients and 389 patients without CHD and indicated sdLDL-C level was more efficacious in predicting coronary severity [ 33 ]. A cohort study from china suggested that increased sdLDL-C were associated with higher risk of CV events in patients with diabetes and stable CAD [ 14 ]. Therefore, the current study might provide valuable further information on the relationship of sdLDL-C and CV events in patients with ACS undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koba S et al recruited 482 stable CHD patients and 389 patients without CHD and indicated sdLDL-C level was more efficacious in predicting coronary severity [ 33 ]. A cohort study from china suggested that increased sdLDL-C were associated with higher risk of CV events in patients with diabetes and stable CAD [ 14 ]. Therefore, the current study might provide valuable further information on the relationship of sdLDL-C and CV events in patients with ACS undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…sdLDL-C has been found to be associated with increased risk for the development of CHD among the healthy participants with high or low risk of CVD [ 12 , 13 ] and increased risk for cardiovascular (CV) events in patients with stable CVD [ 14 ]. However, to date, few studies have explored the role of sdLDL-C in patients with acute coronary syndromes (ACS) undergoing percutaneous coronary intervention (PCI).…”
Section: Introductionmentioning
confidence: 99%
“…There may be other important risk factors to be considered [9][10][11]. The occurrence and development of atherosclerosis (AS) is not only related to the total amount of cholesterol, but may also be closely related to its heterogeneity [12]. According to the size and density, LDL can be divided into different subtypes, including large and light LDL (large buoyant low-density lipoprotein, lbLDL), intermediate-density LDL (intermediate-density lipoprotein, IDL), and small and dense LDL (small dense low-density lipoprotein, sdLDL).…”
Section: Discussionmentioning
confidence: 99%
“…The proatherogenic effect may partly account for the association between AIP and mortality. Moreover, AIP is a surrogate for concentration of atherogenic small dense of LDL particles which may predict all-cause mortality and adverse cardiovascular events [38]. In addition, AIP is associated with the degree of insulin resistance [39].…”
Section: Aip As a Composite Of Tg And Hdl-c Re Ects The Interactionmentioning
confidence: 99%